Downregulation of glob1 mitigates human tau mediated neurotoxicity by restricting heterochromatin loss and elevating the autophagic response in drosophila. - Nisha; Sarkar, S. (Molecular Biology Reports, 2022)
Human neuronal tauopathies are typically characterized by the accumulation of hyperphosphorylated tau in the forms of paired helical filaments and/or neurofibrillary tangles in the brain neurons. Tau-mediated heterochromatin loss and subsequent global transcriptional upsurge have been demonstrated as one of the key factors that promotes tau toxicity. We have reported earlier that expression of human tau-transgene in Drosophila induces the expression of glob1, and its restored level restricts tau etiology by regulating tau hyperphosphorylation and ROS generation via GSK-3?/p-Akt and Nrf2-keap1-ARE pathways, respectively. In view of this noted capability of glob1 in regulation of oxidative stress, and involvement of ROS in chromatin remodeling; we investigate if downregulation of glob1 restores tau-mediated heterochromatin loss in order to alleviate neurotoxicity. The tauV337M transgene was expressed in Drosophila eye by utilizing GAL4/UAS system. Expression of glob1 was depleted in tauV337M expressing tissues by co-expressing an UAS-glob1RNAi transgene by GMR-Gal4 driver. Immunostaining and wstern blot analysis suggested that tissue-specific downregulation of glob1 restores the cellular level of CBP and minimizes tau-mediated heterochromatin loss. It also assists in mounting an improved protective autophagic response to alleviate the human tau-induced neurotoxicity in Drosophila tauopathy models. Our study unfolds a novel aspect of the multitasking globin protein in restricting the pathogenesis of neuronal tauopathies. Interestingly, due to notable similarities between Drosophila glob1 and human globin gene(s), our findings may be helpful in developing novel therapeutic approaches against tauopathies.